Verbal and Visual Signs on “How I Met Your Mother” TV Series Poster - Edelenyi Deme Gabor; Ni Made Suwari Antari; Ni Wayan Sukarini (Jurnal Pendidikan dan Sastra Inggris, 2025)
This research, entitled Verbal and Visual Signs on “How I Met Your Mother” TV Series Poster, focuses on identifying both verbal and visual signs that appear on the official poster of the series and analyzing the meanings they convey. The study applies a qualitative-descriptive method with a semiotic approach, mainly grounded in Chandler’s (2007) theory of semiotics. This is further supported by Dyer’s (1982) theory of verbal and nonverbal signs, as well as Olesen’s (2019) color theory, which enrich the interpretation of the visual elements. The data for this research were collected from official How I Met Your Mother TV Series posters accessed through online sources. The analysis highlights how verbal signs, such as the series title and additional text, function as direct communicators, providing the audience with essential information about the show. At the same time, visual signs play a central role in shaping the poster’s meaning. The representation of the main characters, the recurring image of the iconic yellow umbrella, and the deliberate use of colors in both costumes and background create symbolic layers that reflect the characters’ personalities, relationships, and the overall tone of the narrative. This research demonstrates that a poster is not only a promotional tool but also a semiotic artifact that embodies the essence of the series. Through the interplay of verbal and visual elements, the How I Met Your Mother poster encapsulates the themes of love, friendship, and destiny, which lie at the heart of the storyline and continue to resonate with its audience.